From Theory to Practice: Global Englishes Language Teaching in the Indonesian Context - Budiman, Asep (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2026)
English has evolved from a historically local language into the world’s most widely used global lingua franca, shaped by colonial expansion, economic power, and intensified globalization. Today, English is no longer owned by a small group of so-called native speakers but is used predominantly by multilingual speakers for intercultural communication across diverse global, local, and glocal contexts. Responding to this sociolinguistic reality, this paper synthesizes key insights from Global Englishes scholarship and articulates a comprehensive pedagogical framework consisting of thirteen interrelated dimensions for English language teaching. Drawing on paradigms such as World Englishes, English as a Lingua Franca, and English as an International Language, the paper critically examines how assumptions about language norms, users, pedagogy, assessment, ideology, and teacher education require reconceptualization. Each dimension foregrounds the need to move beyond static, idealized native-speaker models toward dynamic, usage-based, and context-sensitive understandings of English communication. Collectively, the framework highlights the importance of aligning curriculum, instruction, assessment, and teacher beliefs with the plural, multilingual, and ideologically embedded nature of English in the twenty-first century. The paper concludes that a paradigm shift in ELT is both timely and necessary to ensure pedagogical relevance and social responsiveness in an increasingly superdiverse world.